Strategi Taliban dalam Mengambil Alih Pemerintahan Afghanistan - Nizardi Bhakti, Braily Diaz Nizardi Bhakti; Wirawan, Rendy (Interdependence Journal of International Studies, 2025)
The establishment of the Taliban in Afghanistan led to significant conflict and upheaval after the withdrawal of the Soviet Union on February 15, 1989. Initially, the presence of the Taliban was seen as a source of hope for the Afghan community, who longed for stability after the Soviet conflict, which had resulted in a prolonged power struggle. However, that hope faded when the Taliban imposed repressive rules on the Afghan people. In 1996, the Taliban successfully took control of the Afghan government for the first time but collapsed in 2001 due to the US invasion following the 9/11 attacks. During this period, the Taliban faced destruction but eventually regained strength, and in 2021, it once again took control of Afghanistan.This paper aims to explain the strategies used by the Taliban to take over the Afghan government. The author uses Bruce Hoffman's concept of terrorism, supported by the views of other experts, to address the question of what strategies the Taliban employed. The results show that suicide bombings, symbolic violence, and the use of media and propaganda were key elements of the Taliban’s strategy. These approaches contributed to the loss of government credibility and ultimately paved the way for the Taliban to regain control of Afghanistan. Keywords: Taliban, Afghanistan, Taliban Strategy, Terrorism